(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
This paper explores the processing of silicon substrates in microelectronics, specifically mechanical processing, polishing, oxidation, and other treatments, as well as the theoretical modeling of the thermoelectric properties of porous SiNWs.